RANCANG BANGUN SYSTEM KEAMANAN PADA SMARTHOME MENGGUNAKAN APLIKASI ANDROID BERBASIS IOT - Alfa Rizqy, Muhammad Dandy; Paramytha, Nina (Ensiklopedia of Journal, 2024)
Abstract: The development of Internet of Things (IoT) technology has brought significant transformation in various aspects of life, including home security systems. This article describes the design of a security system in a smart home that utilizes IoT-based Android applications. The system is designed to improve home security by utilizing various sensors and connected IoT devices, such as surveillance cameras, fire sensors, and water sensors. Through the developed Android application, users can monitor home conditions in real-time, remotely manage and control security devices, and receive notifications or alerts when suspicious activity is detected, when flooding and fire occur. The development methodology includes designing an integrated system architecture, hardware and software implementation, and system functionality testing. The results of this research show that the IoT-based security system and Android application are able to increase the effectiveness and convenience in managing home security, providing a more flexible and responsive solution to potential security threats. With the ease of access and control offered, this system can be a viable alternative to improve home security in today's digital era. Keywords: internet of things, pear sensor, water sensor, flame sensor, remote control